2007
DOI: 10.1074/jbc.m702870200
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor β Silences Human Papillomavirus-18 Oncogene Expression by Induction of de Novo Methylation and Heterochromatinization of the Viral Control Region

Abstract: Retinoic acid receptor ␤2 (RAR␤2) is often down-regulated during the multistep process to cervical cancer. In that way, its inhibitory function on the transcription factor AP-1, indispensable to maintain human papillomavirus (HPV) gene expression is relieved. Using HPV-18 positive HeLa cells as a model system, we show that ectopic expression of RAR␤2 is able to down-regulate HPV-18 transcription by selectively abrogating the binding of AP-1 to the viral regulatory region in a ligandindependent manner. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…Moreover, there even exists a cross-talk between cis-and transregulatory mechanisms because decreased transcriptional activity due to the presence/absence of a putative trans-repressor/activator can trigger epigenetic alterations (35,36). Such a situation marks promoter sequences for histone modifications and de novo methylation, finally leading to suppression of the respective gene (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there even exists a cross-talk between cis-and transregulatory mechanisms because decreased transcriptional activity due to the presence/absence of a putative trans-repressor/activator can trigger epigenetic alterations (35,36). Such a situation marks promoter sequences for histone modifications and de novo methylation, finally leading to suppression of the respective gene (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…ChIP assays were performed as described previously [47]. Briefly, 1×10 7 of “444” cells were cross-linked with 1% formaldehyde for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it is now clear that the H-ras, N-ras and LAMP3 genes are activated in cervical tumors, whereas KAI1 and galectin-3 genes are inactivated [2,3,4,5]. In addition, it was found that the retinoic acid receptor beta gene is down-regulated in cervical tumors, whereas a gene for telomerase reverse transcriptase is up-regulated [6,7]. We found that the promoter of RASSF1A gene was methylated in squamous cervical carcinoma of Uigur women [8].…”
Section: Clinical Sample Collectionmentioning
confidence: 99%